Design, Synthesis, Investigation, and Application of a Macromolecule Photoswitch - Pang, Juan; Gao, Ziyu; Tan, Huaping; Mao, Xincheng; Wang, Huiming; Hu, Xiaohong (Frontiers in Chemistry, 2019)
Azobenzene (AZO) has attracted increasing interest due to its reversible structural change upon a light stimulus. However, poor fatigue durability and the photobleaching phenomenon restricts its further application. Herein, the AZO domain as a pendent group, was incorporated into copolymers, which was synthesized by radical copolymerization in the research. Structure-properties of synthesized copolymer can be adjusted by monomer ratios. Emphatically, responsive properties of copolymer in different solutions were investigated. In the DMSO solution, copolymer exhibited effective structural change, stable rapid responsive time (1 min) upon UV light at room temperature, stable relative acceptable recovery time (100 min) upon white light at room temperature, and good fatigue resistance property. In an aqueous solution, even more controllable responsive properties and fatigue resistance properties for copolymer were verified by results. More pervasively, the recovery process could be controlled by light density and temperature. In order to clarify reasons for the difference between the AZO molecule and the AZO domain of copolymer, energy barrier or interactions between single atoms or even structural units was calculated using the density functional theory (DFT). Furthermore, the status of copolymer was characterized by dynamic light scattering (DLS) and transmission electron microscope (TEM). Finally, copolymer was further functionalized with bioactive protein (concanavalin, ConA) to reduce the cytotoxicity of the AZO molecule.